ETLAnow: A Model for Forecasting with Big Data – Forecasting Unemployment with Google Searches in Europe - Joonas Tuhkuri (The Research Institute of the Finnish Economy (ETLA), 2016)
In this report we document the ETLAnow project. ETLAnow is a model for forecasting with big data. At the moment, it predicts the unemployment rate in the EU-28 countries using Google search data. This document is subject to updates as the ETLAnow project advances.
Keywords: C22; C53; C55; C82; E27; 330; Big Data; Google; Internet; Nowcasting; Forecasting; Unemployment; Europe; Prognoseverfahren; Suchmaschine; Informationsverhalten; Online-Recherche; Arbeitslosigkeit; EU-Staaten